The Effect of Forum Group Discussion Method towards Student’s Speaking Skill at the Grade Students of Secondary School - Bayu Islam Assasaki (Educational Dynamics: International Journal of Education and Social Sciences, 2025)
This research is about the effect of forum group discussion method towards student’s speaking skill at the tenth-grade student’s. This research aimed to know whether the effect of forum group discussion method towards the students’ speaking skill effectively at the tenth grade of MTs NW MONTONG MAS. This research applied Pre-Assessment, Cycle 1 and Cycle 2. The population of this research was students in the 11th grade and the sample of this research consists of 25 students of MTs NW MONTONG MAS. The Researcher collected the data by giving the pre-assessment, cycle 1 and cycle 2, formulated in an oral test containing the speaking test. The data collected through pre-assessment, cycle 1 and cycle 2 were firstly tabulated and analyzed in percentage. The result could see that the percentages of students’ speaking skill were improved in each cycle. The result of students’ speaking was always positive and increased well, the improvement of students’ speaking skill occurred from pre-assessment until last cycle.